Diagnostic Performance of MRI Versus CT in the Evaluation of Intra-articular Osteochondral Fracture in Pediatric Patients With Acute Traumatic Lateral Patellar Dislocation. Issue 3 (24th March 2022) - Wu, Zhen-Kai; Dai, Zhen-Zhen; Sha, Lin; Li, Hao; Li, Tai-Chun; Zhang, Zi-Ming; Li, Hai
Background: Evaluation of intra-articular osteochondral fractures in children with acute traumatic lateral patellar dislocation (LPD) is important for determining treatment options. Purpose: To (1) compare the diagnostic accuracy of computed tomography (CT) and magnetic resonance imaging (MRI) for evaluating intra-articular osteochondral fractures; (2) compare the interpretation of CT and MRI images between radiologists and pediatric orthopaedic surgeons (POS); and (3) investigate any clinical factors influencing the accuracy of CT and MRI evaluations. Study Design: Cohort study (diagnosis); Level of evidence, 2. Methods: We reviewed 35 knees in 35 patients (mean age, 12.2 ± 1.2 years; 12 boys and 23 girls) who were treated arthroscopically for acute traumatic LPD; 71% of the patients had patellar fractures, 54% had femoral fractures, and 60% had free osteochondral fracture fragments. All presurgical MRI and CT images were reviewed by POS who were blinded to both the reports of the radiologists and surgical records. We compared the accuracy of CT and MRI in diagnosing intra-articular osteochondral fractures against the arthroscopic findings and compared the interpretation of the images by the POS (MRI-O, CT-O) with those of the radiologists (MRI-R, CT-R). Results: There was no significant difference in diagnostic accuracy between CT and MRI for overall intra-articular osteochondral fractures by the POS or the radiologists; however, the CT-O images had a higher diagnostic specificity (84.2% vs 69.6%; P < .001) and sensitivity (88.1% vs 70.1%; P < .001) versus the MRI-R images. Regarding free fracture fragments, the CT-R images had a higher diagnostic accuracy than the MRI-R images (73.5% vs 47.1%; P = .026). When backed by clinical data, the MRI-O images had greater diagnostic accuracy (78.7% vs 60.3%; P = .001) and sensitivity (88.1% vs 30.7%; P = .021) but lower specificity compared with the MRI-R images, and the CT-O images had similar diagnostic accuracy but greater sensitivity than the CT-R images (70.1% vs 52.2%; P < .001). The diagnostic accuracy of MRI-O images was lower for children under 12 years versus children 12 years and over (67.5% vs 83.3%; P = .040). Conclusion: Compared with MRI, CT scans had better diagnostic performance in the evaluation of intra-articular osteochondral fractures in pediatric patients with acute traumatic LPD. Clinical data enhanced the diagnostic sensitivity of MRI and CT but decreased the specificity of MRI. MRI evaluations remain challenging for both POS and radiologists.